Pelatihan Efikasi Diri untuk Menurunkan Burnout pada Perawat di RSU X di Kabupaten Bantul Yogyakarta - Muhammad Hanafi; Rahma Widyana; Siti Noor Fatmah (LPPM Universitas Proklamasi 45, 2021)
This study aims to determine whether self-efficacy training can reduce burnout in nurses in X Bantul General Hospital Yogyakarta. The research subjects were 20 people, divided into the experimental group and the control group. Subject characteristics were male and female nurses with a minimum of 1 year of service, a maximum age of 40 years, having low and moderate self-efficacy and moderate and high burnout. The first research hypothesis, there were differences in burnout after being given self-efficacy training in the experimental group and the control group. The second research hypothesis, there were differences in burnout in the experimental group before and after being given self-efficacy training. The research instrument uses self-efficacy scale, burnout scale, observation, and interview. The results of U-Mann Whitney analysis found the Z post test value of -3.792 with p 0.000 (p <0.01), indicating the difference in burnout was very significant after being given self-efficacy training in the experimental group and the control group. The average burnout of the experimental group was lower (= 52.90) than the control group (= 99.0). Wilcoxon Range Test analysis results found the post test Z value of -2.810 with p 0.005 (p <0.01), showed a significant difference in burnout in the experimental group before and after being given self-efficacy training. The average burnout of the experimental group before being given self-efficacy training was higher (= 96.70) than after being given self-efficacy training (= 52.50).